Do patients regret having in-office vocal fold injections for glottic insufficiency? - Alice Q. Liu; Yunqi Ji; Amanda Hu (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background In-office vocal fold injections (VFI) are an effective treatment for glottic insufficiency. The primary objective of this study was to assess if patients reported decisional regret after VFI. Secondary objectives included determining if variables were associated with lower decisional regret. Methods Case–control study of patients who underwent in-office VFIs for glottic insufficiency from August 2017 to December 2019 at a tertiary laryngology clinic. Participants completed the validated Decision Regret Scale (DRS). Demographic data, clinician’s perceptual analysis with GRBAS (Grade, Roughness, Breathiness, Asthenia, Strain), and patient’s self-reported Voice Handicap Index-10 (VHI-10) were analyzed. Nonparametric tests as well as univariate and multiple logistics regression were performed. Results Of patients eligible, 75% (136/182) completed the DRS (mean age 65.4 years (SD 13.9), 58.1% male). Eighty-three (61.0%) reported no decisional regret, thirty-three (24.3%) reported mild decisional regret, and twenty (14.7%) reported moderate to strong decisional regret. Improvement in most recent VHI-10 (Kendall correlation coefficient tau = 0.156, p = 0.029), Grade of voice (tau = 0.236, p value = 0.002) and Breathiness of voice (tau = 0.150, p = 0.044) were associated with lower DRS. Multivariate logistics regression results showed that the change in Grade of voice (OR 9.9, p < 0.01), Roughness (OR 0.2, p < 0.01) and Breathiness (OR 0.2, p < 0.03) were significantly associated with DRS. Conclusion The majority of patients had no or mild decisional regret after in-office VFI for glottic insufficiency. Both patients who reported less vocal handicap after VFI and clinician-noted improvements in perceptual evaluation of voice after VFI were associated with significantly lower decisional regret. Graphical Abstract